Multi-dimensional adaptive transmission technique for shortto-medium reach optical fiber communication system - Ming TANG; Xi CHEN (Tongxin xuebao)
According to the features of short-to-medium reach optical fiber communication systems,three high performance adaptive modulation and coding schemes were investigated.In the first one,a new dimension,forward error correction (FEC),was introduced to the traditional bit and power loading (BPL) scheme,and the three-dimensional adaptive modulation and coding were achieved.The modulation format and FEC code were allocated based on look-up table (LUT).The proposed algorithm has lower complexity and higher data rate compared to the BPL scheme.The second one was also based on LUT method where one similar data rate with the BPL scheme was achieved using partitioned precoding,but peak-to-average power ratio was reduced up to two dB,and the power efficiency was improved.In the last scheme,probabilistic shaping QAM was adopted as the modulation format,and shaping gain and almost indefinitely fine modulation granularity were achieved at the expense of certain complexity.With adaptive partitioned precoding,without decreasing data rate the number of PS-QAM was limited to reduce the complexity.The experimental results demonstrate that the proposed scheme outperforms the BPL scheme in terms of data rate and receiver sensitivity.